DESIGN ORGANIZATION ADAPTIVE: NAVIGATE TRANSFORMATION SUSTAINABLE MANAGEMENT (JToMO: Journal Transformation of Management and Organization, 2025)
Sustainable management transformation has become a primary necessity in facing increasingly complex global dynamics. This article discusses the concept of adaptive organizational design as a strategy to enhance the competitiveness and sustainability of organizations. With a descriptive qualitative approach, this research explores the uniqueness, novelty, and advantages of adaptive organizational design, as well as the obstacles and solutions in its implementation. This article also proposes a data- and technology-based adaptive organization model to enhance flexibility, innovation, and inclusivity. The results show that the implementation of adaptive organizational design can enhance resilience, creativity, and innovation. The results show that the implementation of adaptive organizational design can enhance resilience, creativity, and innovation.